Associations of Brachial-Ankle Pulse Wave Velocity With Left Ventricular Geometry and Diastolic Function in Untreated Hypertensive Patients - Kwak, Soongu; Kim, Hack-Lyoung; In, Minjae; Lim, Woo-Hyun; Seo, Jae-Bin; Kim, Sang-Hyun; Zo, Joo-Hee; Kim, Myung-A (Frontiers in Cardiovascular Medicine, 2021)
Background: Although brachial-ankle pulse wave velocity (baPWV) is simple and convenient, its usefulness as an initial screening test for hypertensive patients is not well known. This study aimed to investigate the association of baPWV with left ventricular (LV) geometry and diastolic function in treatment-naive hypertensive patients. Methods: A total of 202 untreated hypertensive patients (mean age, 62 years; males, 51.5%) without documented cardiovascular diseases were prospectively enrolled. Both baPWV and transthoracic echocardiography were performed on the same day before antihypertensive treatment. Results: In multiple linear regression analysis after adjustment for potential confounders, baPWV had significant correlations with structural measurements of LV including relative wall thickness (β = 0.219, P = 0.021) and LV mass index (β = 0.286, P = 0.002), and 4 diastolic parameters including septal e′ velocity (β = −0.199, P = 0.018), E/e′ (β = 0.373, P < 0.001), left atrial volume index (β = 0.334, P < 0.001), and maximal velocity of tricuspid regurgitation (β = 0.401, P < 0.001). The baPWV was significantly increased in patients with LV hypertrophy, abnormal LV remodeling, or diastolic dysfunction, compared to those without (P = 0.008, P = 0.035, and P < 0.001, respectively). In the receiver operating characteristic curve analysis, the discriminant ability of baPWV in predicting LV hypertrophy and diastolic dysfunction had an area under the curve of 0.646 (95% confidence interval 0.544−0.703, P = 0.004) and 0.734 (95% confidence interval 0.648−0.800, P < 0.001), respectively. Conclusion: baPWV was associated with parameters of LV remodeling and diastolic function in untreated hypertensive patients. The baPWV could be a useful screening tool for the early detection of adverse cardiac features among untreated hypertensive patients.